Psycholinguistic Aspects of Speech Impact - Mustakimova Kunduz Sobirovna (Genius Journals, 2022)
Speech influence is a deliberate restructuring of the semantic sphere of personality. At the same time, the text of socially oriented communication solves three main psychological tasks. This is, firstly, drawing attention to the text, secondly, optimizing its perception, and thirdly, accepting its content by the recipient. The psycholinguistic features of the text can and should be studied by differentiation depending on their focus on a particular task.
Keywords: speech; influence; communication; psycholinguistics